Randomized single oral dose phase 1 study of safety, tolerability, and pharmacokinetics of Iminosugar UV-4 Hydrochloride (UV-4B) in healthy subjects. - Michael Callahan; Anthony M Treston; Grace Lin; Marla Smith; Brian Kaufman; Mansoora Khaliq; Lisa Evans DeWald; Kevin Spurgers; Kelly L Warfield; Preeya Lowe; Matthew Duchars; Aruna Sampath; et al. (Public Library of Science (PLoS), 2022)
Background UV-4 (N-(9'-methoxynonyl)-1-deoxynojirimycin, also called MON-DNJ) is an iminosugar small-molecule oral drug candidate with in vitro antiviral activity against diverse viruses including dengue, influenza, and filoviruses and demonstrated in vivo efficacy against both dengue and influenza viruses. The antiviral mechanism of action of UV-4 is through inhibition of the host endoplasmic reticulum-resident α-glucosidase 1 and α-glucosidase 2 enzymes. This inhibition prevents proper glycan processing and folding of virus glycoproteins, thereby impacting virus assembly, secretion, and the fitness of nascent virions. Methodology/principal findings Here we report a first-in-human, single ascending dose Phase 1a study to evaluate the safety, tolerability, and pharmacokinetics of UV-4 hydrochloride (UV-4B) in healthy subjects (ClinicalTrials.gov Identifier NCT02061358). Sixty-four subjects received single oral doses of UV-4 as the hydrochloride salt equivalent to 3, 10, 30, 90, 180, 360, 720, or 1000 mg of UV-4 (6 subjects per cohort), or placebo (2 subjects per cohort). Single doses of UV-4 hydrochloride were well tolerated with no serious adverse events or dose-dependent increases in adverse events observed. Clinical laboratory results, vital signs, and physical examination data did not reveal any safety signals. Dose-limiting toxicity was not observed; the maximum tolerated dose of UV-4 hydrochloride in humans has not yet been determined (>1000 mg). UV-4 was rapidly absorbed and distributed after dosing with the oral solution formulation used in this study. Median time to reach maximum plasma concentration ranged from 0.5-1 hour and appeared to be independent of dose. Exposure increased approximately in proportion with dose over the 333-fold dose range. UV-4 was quantifiable in pooled urine over the entire collection interval for all doses. Conclusions/significance UV-4 is a host-targeted broad-spectrum antiviral drug candidate. At doses in humans up to 1000 mg there were no serious adverse events reported and no subjects were withdrawn from the study due to treatment-emergent adverse events. These data suggest that therapeutically relevant drug levels of UV-4 can be safely administered to humans and support further clinical development of UV-4 hydrochloride or other candidate antivirals in the iminosugar class. Trial registration ClinicalTrials.gov NCT02061358 https://clinicaltrials.gov/ct2/show/NCT02061358.